Reactive transport controls on sandy acid sulfate soils and impacts on shallow groundwater quality. Issue 6 (18th June 2014) - Salmon, S. Ursula; Rate, Andrew W.; Rengel, Zed; Appleyard, Steven; Prommer, Henning; Hinz, Christoph
Abstract Disturbance or drainage of potential acid sulfate soils (PASS) can result in the release of acidity and degradation of infrastructure, water resources, and the environment. Soil processes affecting shallow groundwater quality have been investigated using a numerical code that integrates (bio)geochemical processes with water, solute, and gas transport. The patterns of severe and persistent acidification (pH < 4) in the sandy, carbonate‐depleted podzols of a coastal plain could be reproduced without calibration, based on oxidation of microcrystalline pyrite after groundwater level decrease and/or residual groundwater acidity, due to slow vertical solute transport rates. The rate of acidification was limited by gas phase diffusion of oxygen and hence was sensitive to soil water retention properties and in some cases also to oxygen consumption by organic matter mineralization. Despite diffusion limitation, the rate of oxidation in sandy soils was rapid once pyrite‐bearing horizons were exposed, even to a depth of 7.5 m. Groundwater level movement was thus identified as an important control on acidification, as well as the initial pyrite content. Increase in the rate of Fe(II) oxidation lead to slightly lower pH and greater accumulation of Fe(III) phases, but had little effect on the overall amount of pyrite oxidized. Aluminosilicate (kaolinite) dissolution had a small pH‐buffering effect but lead to the release of Al and associated acidity. Simulated dewatering scenarios highlighted the potential of the model for risk assessment of (bio)geochemical impacts on soil and groundwater over a range of temporal and spatial scales.